Study on aerated concrete using steam curing test method - Naidu T Y Rohith; Satyanarayana G.V.V (E3S Web of Conferences, 2021)
The Accumulation of warm and moisture in building walls plays an vital role in its upkeep and power conservation. Aerated Concrete block, an environmental material gives an anticipated result to building construction. Aerated Concrete can build light weight, eco-friendly, non-structural wall, reduced dead weight concrete blocks. Aerated Concrete is developed introducing aluminium powder which reacts with the calcium hydroxide on hydration of cement. Several curing test methods are done to find out the optimum dosage of aluminium content. The Aerated concrete blocks are pre-casted by mixing Portland cement, fly ash, GGBS, quarry dust, lime stone powder, water and aluminium powder.